Acculturation of Islam in Kabumi Cultural Tradition of Lebuawu Village Jepara - Nuha, Muchammad Ulin (el Harakah: Jurnal Budaya Islam, 2024)
This study examines the acculturation of Islam in the implementation of the Kabumi tradition in Lebuawu Village, Pecangaan District, Jepara Regency, Central Java. It employed a qualitative descriptive method to describe the cultural facts surrounding the traditional Kabumi celebration. The findings show that the Kabumi tradition has become a traditional celebration as a form of gratitude by the people of Lebuawu Village to the Creator for allowing them to live on Earth by His grace. They heavily rely on the earth to grow crops, obtain food and drink, and carry out other activities. As a result, they perform earth alms as a way to express their gratitude to the earth. Additionally, the alms to the earth also represent a form of gratitude for the salvation and sustenance received by the community, and are believed to bring protection to their fields, ensuring abundant harvests. The acculturation of Islam in the implementation of Kabumi also teaches the community to always maintain an attitude of tolerance among people of different religions, as this acculturation preserves local traditions that characterize this custom. Penelitian ini mengkaji tentang akulturasi Islam dalam pelaksanaan tradisi Kabumi di Desa Lebuawu, Kecamatan Pecangaan, Kabupaten Jepara, Jawa Tengah. Penelitian ini menggunakan metode deskriptif kualitatif untuk mendeskripsikan fakta budaya seputar perayaan adat Kabumi. Temuan penelitian menunjukkan bahwa tradisi Kabumi telah menjadi perayaan adat sebagai wujud rasa syukur masyarakat Desa Lebuawu kepada Sang Pencipta yang telah mengizinkan mereka hidup di bumi atas karunia-Nya. Mereka sangat bergantung pada bumi untuk bercocok tanam, memperoleh makanan dan minuman, serta melakukan aktivitas lainnya. Oleh karena itu, mereka melakukan sedekah bumi sebagai wujud rasa syukurnya terhadap bumi. Selain itu, sedekah bumi juga merupakan wujud rasa syukur atas keselamatan dan rezeki yang diterima masyarakat, serta dipercaya dapat memberikan perlindungan pada ladangnya dan menjamin hasil panen yang melimpah. Akulturasi Islam dalam pelaksanaan Kabumi juga mengajarkan masyarakat untuk selalu menjaga sikap toleransi antar umat yang berbeda agama, karena akulturasi ini melestarikan tradisi lokal yang menjadi ciri adat tersebut.